2011
DOI: 10.1089/ten.tec.2010.0072
|View full text |Cite
|
Sign up to set email alerts
|

Macroporous Hydrogel Scaffolds and Their Characterization By Optical Coherence Tomography

Abstract: A simple porogen-leaching method to fabricate macroporous cyclic acetal hydrogel cell scaffolds is presented. Optical coherence tomography (OCT) was applied for nondestructive imaging and quantitative characterization of the scaffold structures. High-resolution OCT reveals the microstructures of the engineered tissue scaffolds in three dimensions. It also enables subsequent image processing to investigate quantitatively several key morphological design parameters for macroporous scaffolds, including the volume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 75 publications
0
47
0
Order By: Relevance
“…Future studies are also needed to cross-validate the blood flow measured by DOCT with confocal or two-photon microscopy by using multi-modal optical systems [7073]. …”
Section: Discussionmentioning
confidence: 99%
“…Future studies are also needed to cross-validate the blood flow measured by DOCT with confocal or two-photon microscopy by using multi-modal optical systems [7073]. …”
Section: Discussionmentioning
confidence: 99%
“…Reprinted with permission from Ward et al 84 (B) OCT imaging to characterize EH-PEG hydrogels fabricated using different formulations in terms of volume porosity, interconnectivity, and pore size. Reprinted with permission from Chen et al 93 (C) In vivo monitoring of human adipose tissuederived stromal mesenchymal cell differentiation in subcutaneous implanted demineralized bone matrix scaffolds using bioluminescence imaging. Reprinted with permission from Bago et al 104 Color images available online at www.liebertpub.com/teb constructs are enabled with the penetration depth increased up to *500 mm.…”
Section: Optical Imagingmentioning
confidence: 99%
“…As a result, in vitro studies using OCT demonstrated the ability to quantify volume porosity and pore size of macroporous hydrogel scaffolds nondestructively, as shown in Figure 7B. 93 Also, development of tissue-engineered skin was monitored over time using OCT because it does not require sectioning or staining of the samples, as in the case of fluorescence microscopy. In addition, due to its relative noninvasiveness, OCT has been applied to clinical studies, especially including intravascular imaging.…”
Section: Optical Imagingmentioning
confidence: 99%
“…4,6,7 A number of fabrication techniques have been developed to generate pores within hydrogels for tissue engineering applications, including electrospinning, 8,9 gas foaming, [10][11][12][13] freeze-thaw, 14,15 phase separation, [16][17][18][19] and salt leaching. [20][21][22] However, the majority of these techniques for generating macroporous hydrogels often involve cytotoxic procedures or chemicals that undermine a key advantage hydrogels have over other traditional tissue engineering scaffolds: the ability to encapsulate viable cells with a homogeneous distribution within the 3D scaffold during fabrication. 4,23 Subsequent cell seeding in such scaffolds may lead to low seeding efficiency and a heterogeneous cell distribution, particularly without proper pore interconnectivity.…”
Section: Introductionmentioning
confidence: 99%